The Causal Relationship between Trading Volume and Return Volatility with Interest Rate and Exchange Rate as Exogenous Variables (Empirical Research on Property Indexes of Indonesia, Malaysia, Philippines, and Thailand) - Permanawati, Rahmadani Nur; Witiastuti, Rini Setyo; Nugraha, Mahardika Dandy; Maharani, Rr. Annisa Tri Safira (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2022)
This study aims to analyze the causal relationship between trading volume and return volatility along with macroeconomic variables such as interest rates and exchange rate. The endogenous variables in this study are trading volume and return volatility, while the exogenous variables are interest rates and exchange rates. The sample used in this research is property indexes in Indonesia, Malaysia, Philippines, and Thailand who provide monthly data for the four variables during the observation period in January 2012-December 2019. The analysis technique used to test the hypothesis in this study is Vector Autoregression (VAR) technique. The result of this study indicate that trading volume has positive effect on return volatility in property indexes of Indonesia, Philippines, and Thailand, meanwhile trading volume has no effect on return volatility in Malaysia’s property index. Return volatility has no effect on trading volume in all the countries whether in Indonesia, Malaysia, the Philippines, or in Thailand. There is a one-way causality relationship between trading volume and return volatility in property indexes of Indonesia, Philippines, and Thailand. There is no causality relationship between trading volume and return volatility in Malaysia’s property index.